Coactivity of Mast Cells and Stem Cells on Angiogenesis and Antioxidants' Potentials at Inflammation, Proliferation, and Tissue Remodeling Phases of Wound - Mousavi, Mahshad; Khanifar, Ahmad; Mousavi, Nazanin; Anbari, Khatereh; Chehelcheraghi, Farzaneh (Archives of Plastic Surgery, 2022)
Background Reactive oxygen species cause serious damage to the physiological function of tissues. Determination of total antioxidant capacity of skin tissue is one of the determinants of damaged tissue function. Mast cells (MCs) are one of the groups of cells that are invited to the site of injury. The healing process begins with the rapid release of various types of MCs' intermediate factors at the site of injury. Bone marrow mesenchymal stem cell (BMMSC) production and secretion have been shown to regenerate the skin. The aim of this research was to evaluate the wound-healing and antioxidant effects of BMMSCs per MCs.Methods Fifty-four albino Wistar male rats were divided into three groups: (1) nonsurgery, (2) surgery, and (3) surgery + BMMSCs. Groups 2 and 3 were operated with a 3 × 8 cm flap and in group 3, cell injections (7 × 109 cell injection at the time of surgery) were performed. After days 4, 7, and 15, percentage of the surviving tissue, histological characteristics, superoxide dismutase (SOD) activity, and amount of malondialdehyde (MDA) were measured in the groups. For results, Graph Pad Prism 8 software was used, and data were analyzed and compared by analysis of variance and Tukey test.Results BMMSCs' application decreased the amount of MDA, increased SOD activity and survival rate of the flaps, and improved the histological characteristics.Conclusion This study revealed the protective effects BMMSCs alongside MCs against oxidative stress on the survival of the flaps. However, for clinical use, more research is needed to determine its benefits.
Keywords: reactive oxygen species; antioxidant; superoxide dismutase; wound healing